Theoretical approaches of interval-valued fuzzy code and fuzzy soft code - Masresha Woldie; Jejaw Mebrat; Mihret Taye (Journal of Fuzzy Extension and Applications)
In this study, we attempted to demonstrate the interval-valued fuzzy code by extending the concept of an interval-valued fuzzy set. Further, we discussed the operations of the interval-valued fuzzy code. The interval-valued fuzzy soft code is introduced, and various related properties are investigated in this paper. Finally, we show that the operations of interval-valued fuzzy soft code are discussed. Through this paper, we use the set of integers modulo 2, that is = {0, 1}.